(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Cancer stem cell markers known for their ability to induce tumor initiation, angiogenic activity, therapy resistance and metastasis formation. Plant extract potentially was used to treat cancer and/or target its genes. Cyperus rotundus tubers extract has been used in ancient as a folk medicine for its antibacterial, anti-diabetic and for other maladies for its antioxidant properties that have been estimated in modern medicine. Objective: To determine the effects of total oligofalvonoids (TOF) extracted from Cyperus rotundus tubers against cervical cancer cells line (HeLa) and human glioblastoma (AMGM) cell line. Methods: Cytotoxicity of TOF extract against both cancer cell lines was determined after 24 hr of exposure and the best concentration of inhibition was 350 µg/ml. Total RNA extracted from both cell lines after treated with TOF and the expression levels of cancer stem cell markers OCT3/4 as well as matrix metalloproteinasese MMP2 and MMP9 have been measured using quantitative real time polymerase chain reaction. Results: Cytotoxicity of TOF extract with concentration (350 µg/ml) shown to reduce the growth of cancer cell lines after 24 hr of exposure. The expression level of OCT3/4 was highly significantly reduced in both AMGM and HeLa cells after treated with TOF and the fold change reduced from (15 to 0.03) and (10 to 0.09), respectively. On the other hand, the expression levels of MMP2 and MMP9 were significantly decreased in AMGM and HeLa cells treated with TOF extract with decreasing in fold change from (10.2 to 0.02) for MMP2 in AMGM cells and (1.85 to 0.5) for MMP9. And fold change of MMP2 expression in HeLa cells was decreased after treated with TOF from (11.1 to 0.01) and for MMP9 (11.43 to 0.08). Conclusion: The result indicates that the inhibition of cancer stem cell markers OCT3/4 and MMP2 and MMP9 may provide a novel strategy to treat cancer using a natural plant extract. Keywords: Cancer stem cell markers, AMGM cells, Hela cells Citation: Abdulghany ZS, Mahmood NA, Tawfeeq AT, Yassen NY. Cyperus Rotundus Tubers extract inhibits stem cell markers expression in cervical and human glioblastoma cancer cell lines. Iraqi JMS. 2018; 16(2): 159-165. doi: 10.22578/IJMS.16.2.7